The geographical forecast of stability of development of ethnogeosystem of Kalmyk people - D. S. Klimov (Юг России: экология, развитие)
In clause the forecast of development of ethnogeosystem of Kalmyk people is given, the periods of its greatest and least stability are revealed. Stability of development of elements EGS was estimated on a number of criteria. As a technique of geographical forecasting the technique of an individual expert estimation is selected. Research covered more than a 350-years time piece. For greater adequacy this piece has been divided into the basic periods separated by historical events or processes, affected on stability of development EGS.